Digital Education In Learning Arabic Among Non-Native Speakers In China/ التعليم الرقمي في تعلم اللغة العربية لدى الطلبة الناطقين بغيرها في الصين - Ismail, Zawawi; Xu, Ma; Odeh, Mohammad Ibrahim (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This study aims to explore the level of digital education usage in learning Arabic among non-native speakers at a Chinese university, and to examine the influence of gender and duration of language teaching on this usage. The study adopted a descriptive analytical approach and utilized a questionnaire distributed to 151 students studying at Northwest Normal University. Data were analyzed using SPSS software, and the questionnaire focused on three main domains: digital learning channels, academic areas, and accessibility. The results showed that the overall digital education usage was at an “upper-medium” level, with no statistically significant differences related to gender or length of language learning. These findings indicate a general consistency in technology usage across different student groups, highlighting the importance of a supportive digital environment in promoting equal learning opportunities.